2017
DOI: 10.3892/ijmm.2017.2863
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-382 by propranolol inhibits the progression of infantile hemangioma via the PTEN-mediated AKT/mTOR pathway

Abstract: Approximately 10% of infantile hemangiomas (IHs) are the most common vascular tumors affecting children and are characterized by rapid growth, and can have destructive, disfiguring and even life-threatening consequences. Currently, propranolol is considered to be a safe and effective treatment option for problematic proliferating IHs. Recent studies have also revealed that microRNAs (miRNAs or miRs) play important roles in the regulation of angiogenesis. In this study, XPTS‑1 cells were used as a hemangioma-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Recently, miR-4295 is found to be a novel oncogenic miRNA in non-small cell lung cancer. 35 We hypothesized that miR-4295 might be involved in the progress of propranolol regulating IH. 34 Whereupon, we examined miR-4295 expression in IH tissues and adjacent tissues, and results showed that miR-4295 expression was significantly upregulated in IH tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-4295 is found to be a novel oncogenic miRNA in non-small cell lung cancer. 35 We hypothesized that miR-4295 might be involved in the progress of propranolol regulating IH. 34 Whereupon, we examined miR-4295 expression in IH tissues and adjacent tissues, and results showed that miR-4295 expression was significantly upregulated in IH tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher angiostatin level was seen among HF patients using beta blocker therapy than in those who did not. There is some research in the literature about the effect of beta blockers on angiogenesis related to the effects of propranolol in infantile hemangioma and the anti-angiogenic effect of beta blockers in breast cancer patients [17,18]. According to our findings, we hypothesize that the use of beta blockers may reduce angiogenesis via increasing angiostatin in HF patients with CKD.…”
Section: Discussionsupporting
confidence: 58%
“…The mature gene locus were chr14:101,054,316-101,054,337, and the base sequence was GAAGUUGUUCGUGGUGGAUUCG , with a length of 22 nt. (Fig.1) 2.1.2 hsa-miR-382-5P participates in disease regulation Using PubMed to retrieve the related literature of miR-382-5P, we found that miR-382-5P was upregulated in acute promyelocytic leukemia [7,8] , atherosclerosis [12] ,breast cancer [4] ,epidural fibrosis [10] , primary myelofibrosis [9] , primary liver cancer [11] ,cervical cancer [13] , but down-regulated in glioma [5,6] ,oral squamous cell carcinoma [3] ,miR-382 was down-regulated in non-small cell lung cancer [14,15] , osteosarcoma [16] , prostate cancer [19] ,ovarian cancer [20] , primary liver cancer [24] , colorectal cancer [21,22] , while schizophrenia [25] ,diabetic nephropathy [17] , IgA nephropathy [18] ,infantile hemangioma [23] . Thus, the expression of miR-382-5P is tissue-specific, and it is involved in the regulation of cell viability, migration, invasion, angiogenesis, proliferation, cell differentiation, oxidative stress and other biological behaviors.…”
Section: Data Analysis Of Tcga Databasementioning
confidence: 99%
“…A series of nucleases obtained mature miR-382-5P and miR-382-3P by cutting and editing miR-382, in which miR-382-5P was located in the long arm of chromosome 14. In recent years, many studies have shown that the expression of miR-382-5P is abnormal in oral squamous cell carcinoma [3] ,breast cancer [4] ,glioma [5,6] ,acute promyelocytic leukemia [7,8] ,primary myelofibrosis [9] ,epidural fibrosis [10] ,primary liver cancer [11] ,atherosclerosis [12] ,cervical cancer [13] ,miR-382 is abnormal in non-small cell lung cancer [14,15] , osteosarcoma [16] , diabetic nephropathy [17] , IgA nephropathy [18] prostate cancer [19] ,ovarian cacner [20] ,colorectal cancer [21,22] ,infantile hemangioma [23] ,primary liver cancer [24] ,schizophrenia [25] , which are closely related to the proliferation, differentiation, migration, invasion, drug resistance and other biological processes of tumor cells. However, the expression and clinical significance of miR-382-5P in ovarian cancer have not been reported.…”
Section: Introductionmentioning
confidence: 99%